Superior segmental optic hypoplasia as a differential diagnosis of glaucoma - Yamamoto, Tetsuya (Taiwan J Ophthalmol, 2019)
Superior segmental optic hypoplasia (SSOH) is a congenital anomaly affecting the optic nerve head and retina. Although the conventional characterization of SSOH emphasizes the relatively superior entrance of the central retinal artery, the pallor of the superior optic disc, a superior peripapillary halo, and thinning of the superior nerve fiber layer, we encounter many cases with rim thinning in the superior nasal region that corresponds to a nerve fiber layer defect and an inferior wedge-shaped visual field defect connecting to the blind spot. However, among Asians, such cases usually lack pallor of the superior optic disc and more resemble glaucomatous optic neuropathy. We found the prevalence of SSOH to be 0.2%/eye and 0.3%/case among Japanese. We also noted that approximately half of all SSOH eyes show visual field changes. SSOH is an important differential diagnosis of glaucoma, especially normal-tension glaucoma, in Asian populations.